Validity of the Japanese version of the REM Sleep Behavior Disorder (RBD) Screening Questionnaire for detecting probable RBD in the general population. Issue 8 (5th April 2015) - Nomura, Takashi; Inoue, Yuichi; Kagimura, Tatsuo; Kusumi, Masayoshi; Nakashima, Kenji
<x xml:space="preserve">Abstract</x> Aims In order to evaluate the validity of the REM Sleep Behavior Disorder (RBD) Screening Questionnaire (RBDSQ) as a screening tool for RBD in a general population setting, we conducted a validation study using residents of a rural community. Methods We sent questionnaires that included the RBDSQ to 2631 eligible adult residents in the town of Daisen, Japan. Results Of those residents, 1572 participants (59.7%) gave complete answers to the RBDSQ. Among them, 179 participants (11.4%) scored ≥5 points on the questionnaire; an additional 149 participants scoring ≤4 points were randomly selected for further telephone interview. Based on obtained results, nine participants (0.57%) were judged as having probable RBD. Receiver–operator curve analysis revealed that a total score of 6 points on the RBDSQ represented the best cut‐off value for detecting probable RBD (sensitivity: 100%; specificity: 73.0%). Analysis based on the item response theory revealed that items 1, 4, 6‐1, 7, and 8 had lower difficulty than the remaining items, suggesting that these items are more essential in the screening for probable RBD. Conclusions The present study revealed that a score of 6 points on the RBDSQ could be used as a cut‐off value for the screening of probable RBD in the general population. Evaluation of the distribution of positive items might be helpful for identifying the intensity of a person's RBD symptoms.